The Dialectics of Religious and Cultural Liberalism in The Transcultural Era - Hidayatullah, Muhammad Fahmi; Firdausi, Muhammad Anwar; Hanafi, Yusuf; Ismail, Zawawi (UIN Maulana Malik Ibrahim Malang, 2021)
Trans culture is a cross-cultural condition which can develop or survive within the life of a community. Religion and culture as the pillars for unity in the cross-cultural era can potentially develop into liberalism. This study aims to reveal the process of religious and cultural liberalism along with the solutions. It uses a qualitative-analysis method with hermeneutic approach based on the thoughts of the figures of Nahdlatul Ulama (NU) in East Java. To collect the data, the researchers conduct in-depth interviews and data analysis of the works and news on religious and cultural liberalism. The study discovers the dialectic model of religious liberalism by making human rights the main source of law, which is called theological-capitalism. Besides, it finds cultural liberalism in the form of an identity crisis, which is called enculturation-liberalism. To overcome the religious liberalism, we can use clarification techniques and logical-systematic thinking. Meanwhile, the solution to deal with cultural liberalism is through cultural realism and socio-cultural learning. Transkultural adalah kondisi lintas kebudayaan yang dapat berkembang atau bertahan di kehidupan masyarakat. Agama dan budaya sebagai pilar persatuan yang dalam era lintas kebudayaan berpotensi berkembang pada paham liberal. Tujuan penelitian ini mengungkap proses liberalisme agama dan budaya yang disertai solusi dalam menangkalnya. Metode penelitian yang digunakan adalah kualitatif-analisis dengan pendekatan hermeneutik berdasarkan pemikiran tokoh Ulama’ NU Jawa Timur. Dalam menggali data, dilakukan interviu mendalam serta analisis data dokumentatif karya dan berita liberalisme agama dan budaya. Hasil penelitian ditemukan model dialektika liberalisme agama dengan menjadikan Hak Asasi Manusia sebagai sumber hukum utama disebut teologis-kapitalistik, sedangkan dialektika liberalisme budaya dalam bentuk krisis identitas disebut enkulturasi-liberalistik. Solusi dalam menaggulangi liberalisme agama dengan menggunakan teknik klarifikasi dan berfikir logis-sistematis. Sedangkan solusi menghadapi liberalisme budaya melalui realisme culture dan socio-culture learning.